The Level of Organizational Management Conflict for Public Secondary Schools Principals and its Relationship with the Level of Organizational Loyalty for Teachers in the Capital Amman - Abu Snaina, Awnia; Al-Biati, Abdul Jabbar (Jordan Journal of Educational Sciences, 2014)
Abstract: This study aimed at investigating the relationship between organizational management conflicts for public secondary schools principals with organizational loyalty for teachers from teachers point of view in the capital Amman. A sample of (200) teachers was chosen. Two quesionaires were developed and their validity and reliability were achieved. The main results were as follows: The level of organizational management conflict for public secondary schools principals was medium , and the level of organizational loyalty for teachers was medium. There was a significant relationship between the level of organizational management conflict for principals and the level of organizational loyalty for teachers from teachers’ point of view. and there was a significant difference in the level of organizational management conflict according to respondents gender for female, teacher rank for expertise teacher and for education district for Amman II education district no significant differences according to other variables. and there were no significant differences in organizational loyalty in all variables. In the light of the results the study recommended organizing training programs for the principals in the organizational management conflict focusing on its concept, importance and management strategies.